Al-10%Si-2%Cu-1%Mg-0.5%Mn 합금 주괴의 고온변형 - 장준연; 문인기 (대한금속·재료학회, 2002)
Hot compression test was performed on Al-10%Si-2%Cu-1%Mg-0.5%Mn ingot in the temperature range 440∼500℃ and in the strain rate range 0.1∼10/sec in order to understand the hot deformation features and to explore the possibility of uniform distribution of eutectic Si particles. A typical stress-strain curve was well established where the stress increases sharply in the beginning of the deformation, and then decreases gradually in the strain rate of 0.5∼10/sec. Apparent activation energy of 65 ㎉/㏖ and stress exponent of 8.4 were evaluated from the peak stress. Deformation at low strain rate and high temperature is favorable in view of low flow stress and relatively uniform distribution of Si particles. Hard Si eutectics between primary Al grains begin to deform after soft Al grains are easily elongated in an early stage of the deformation. This type of deformation mode strongly demands at least 0.7 true strain to break the net-work structure of eutectic Si effectively. It is suggested that suitable heat treatment prior to the hot deformation be employed to ensure uniform distribution of fine Si particles.